CS-semi5 Inhibits NF-κB Activation to Block Synovial Inflammation, Cartilage Loss and Bone Erosion Associated With Collagen-Induced Arthritis - Li, Xiang; Tang, Xiaonan; Wang, Yufei; Chai, Changwei; Zhao, Zhehui; Zhang, Haijing; Peng, Ying; Wu, Lianqiu (Frontiers in Pharmacology, 2021)
Rheumatoid arthritis (RA) is a chronic, systemic autoimmune disease that affects 1% of the population. CS-semi5 is a semisynthetic chondroitin sulfate by our institute. In this study, CS-semi5 was shown to have positive effects on a model of CIA. CS-semi5 treatment had obvious effects on weight loss and paw swelling in CIA mice. Post-treatment analysis revealed that CS-semi5 alleviated three main pathologies (i.e., synovial inflammation, cartilage erosion and bone loss) in a dose-dependent manner. Further study showed that CS-semi5 could effectively reduce TNF‐α and IL‐1β production in activated macrophages via the NF‐κB pathway. CS-semi5 also blocked RANKL-trigged osteoclast differentiation from macrophages. Therefore, CS-semi5 may effectively ameliorate synovial inflammation, cartilage erosion and bone loss in RA through NF-κB deactivation.